2007
DOI: 10.1016/j.lmot.2006.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Repeated cocaine experience facilitates sucrose-reinforced operant responding in enriched and isolated rats

Abstract: The purpose of the present experiment was to determine whether repeated cocaine exposure differentially affects sucrose-reinforced operant responding in rats raised in an enriched condition (EC) or an isolated condition (IC). Specifically, the performance of EC and IC rats pressing a lever for sucrose under a high fixed-ratio schedule (FR 30) prior to and after 10 days of exposure to cocaine (15 mg/kg, i.p.) or saline was compared. Regardless of rearing condition, rats repeatedly exposed to cocaine had shorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…Arguing against this possibility, however, enhanced conditioned approach was observed on the first trial of the Pavlovian reminder session, which suggests that the rats possessed an altered response to the CS prior to any re-training sessions. Unlike previous studies, no effects of amphetamine sensitization on instrumental response rates were observed (Klein et al 2007; Mendez et al 2009; Nordquist et al 2007). One possibility for this difference is that the response requirement used here was not appropriate to detect effects of amphetamine sensitization.…”
Section: Discussioncontrasting
confidence: 98%
“…Arguing against this possibility, however, enhanced conditioned approach was observed on the first trial of the Pavlovian reminder session, which suggests that the rats possessed an altered response to the CS prior to any re-training sessions. Unlike previous studies, no effects of amphetamine sensitization on instrumental response rates were observed (Klein et al 2007; Mendez et al 2009; Nordquist et al 2007). One possibility for this difference is that the response requirement used here was not appropriate to detect effects of amphetamine sensitization.…”
Section: Discussioncontrasting
confidence: 98%
“…The current findings add to a growing literature showing that repeated drug administration can enhance appetitive behaviors generated by non-drug rewards. [29], [30], [34][37], [51], [61][65]. Such findings suggest that extended drug exposure produces nonspecific alterations in motivation, perhaps via adaptations in the dopamine system.…”
Section: Discussionmentioning
confidence: 92%
“…These findings suggest a dissociation between the effects of chronic cocaine on probabilistic and delay discounting in rats, which is supported by findings in human cocaine users showing no correlation between performance on delay and probabilistic decision-making tasks (Monterosso et al, 2001), as well as by data in rats showing no correlations between performance on these two tasks (Simon, Gilbert, Mayse, Bizon, & Setlow, 2009). Furthermore, the dissociation between the effects of chronic cocaine in these two tasks suggests that the elevated impulsive choice in the delay discounting task was due primarily to cocaine’s effects on factors specific to temporal decision-making, rather than on general factors such as increases in incentive motivation, changes in sensitivity to reward magnitude, or discriminative ability, although it is possible that the longer withdrawal time at which rats were tested in the probabilistic discounting task may have reduced cocaine’s effects (Deroche, Le Moal, & Piazza, 1999; Klein, Gehrke, Green, Zentall, & Bardo, 2007; Mendez et al, 2008; Roesch et al, 2007). Interestingly, the opposite pattern of effects in these two decision-making tasks has been observed following several weeks of withdrawal from chronic experimenter-administered amphetamine, which has no effect on delay discounting but increases choice of the large uncertain reward in the probabilistic discounting task (Floresco & Whelan, 2009; Stanis, Marquez Avila, White, & Gulley, 2008)—note that although increases in impulsive choice have been observed during chronic amphetamine administration, these effects do not endure for more than a few days of withdrawal (Gipson & Bardo, 2009).…”
Section: Discussionmentioning
confidence: 99%